The influence of the behavior of using artificial intelligence (AI) on the self-efficacy of UNM Guidance and Counseling students - Aryani, Farida; Rais, Muhammad; Kasim, Sinta Nurul Oktaviana; Pratiwi, Dewi (Program Studi bimbingan Konseling PPs UNM Makassar, 2025)
This study examines the relationship between the behavior of using Artificial Intelligence (AI) specifically ChatGPT and the self-efficacy of Guidance and Counseling students at Universitas Negeri Makassar, as well as explores differences based on gender. A quantitative correlational approach was employed with 171 fifth-semester students selected through stratified random sampling to ensure proportional representation of each class. The instruments used were the AI usage behavior scale and the General Self-Efficacy Scale (GSES), with data collected online. Descriptive statistics and Pearson correlation analysis revealed a positive relationship between ChatGPT usage and self-efficacy, as indicated by the high categories in the magnitude (70,8%), strength (77,2%), and generality (98,8%) dimensions. Additionally, no significant differences in self-efficacy were found based on gender. These findings highlight that AI utilization contributes to enhancing students’ academic self-confidence and underscores the importance of digital literacy in optimizing AI use.